The Influence of Service Quality on Outpatient Satisfaction at Pintu Sehat Mahulu Pratama Hospital - Nikolaus Jeno; Lamri; Ratanto (Formosa Journal of Science and Technology, 2023)
Health effort is any activity to maintain and improve health, aiming to achieve optimal health status for the community. This research is a quantitative study with a cross-sectional approach using the non-probability sampling method, which is taking samples that are not based on calculated probabilities. The sampling technique in this study was the respondent's purposive sampling technique. This research instrument uses a questionnaire that has been used in previous research. The time of the research was conducted in February-March 2023 at the Pintu Sehat Mahulu Hospital. Furthermore, the data were analyzed using the chi square test. Service quality significantly affects patient satisfaction undergoing outpatient care at the Gateway Sehat Mahulu Primary Hospital. There is a relationship between service quality variables and satisfaction of outpatients at the Gateway Sehat Mahulu Hospital.